Reproducibility of limb power outputs and cardiopulmonary responses to exercise using a novel swimming training machine - Swaine, I. L.; Hunter, A. M.; Carlton, K. J.; Wiles, J. D.; Coleman, D. (International Journal of Sports Medicine, 2010)
The purpose of this study was to determine the reproducibility of limb power outputs and cardiopulmonary responses, to incremental whole-body exercise using a novel swimming training machine. 8 swimmers with a mean age of 23.7±4.6 (yrs), stature 1.77±0.13 (m) and body mass of 74.7±2.8 (kg) gave informed consent and participated in repeat exercise testing on the machine. All subjects performed 2 incremental exercise tests to exhaustion using front crawl movements. From these tests peak oxygen consumption (VO2peak), peak heart rate (HRpeak), peak power output (Wpeak) and individual limb power outputs were determined. Results showed there were no significant differences between test 1 and 2 for any variable at exhaustion, and the CV% ranged from 2.8 to 3.4%. The pooled mean values were; VO2peak 3.7±0.65 L.min-1, HRpeak 178.7±6.6 b.min-1 and Wpeak 349.7±16.5 W. The mean contributions to the total power output from the legs and arms were (37.3±4.1% and 62.7±5.1% respectively). These results show that it is possible to measure individual limb power outputs and cardopulmonary parameters reproducibly during whole-body exercise using this training machine, at a range of exercise intensities.